Toileting Disability in Older People Residing in Long-term Care or Assisted Living Facilities: A Scoping Review of the Literature. Issue 5 (September 2019) - Yeung, Jasper; Jones, Allyson; Jhangri, Gian S.; Gibson, William; Hunter, Kathleen F.; Wagg, Adrian
Abstract : For purposes of this review, we defined toileting disability as a result of practices, procedures, or conditions that result in an individual requiring assistance using the bathroom. This scoping review synthesizes existing knowledge of extrinsic and/or intrinsic factors that might lead to or be associated with toileting disability and identified knowledge gaps related to toileting disability in older adults residing in long-term care or assisted living facilities. A search of 9 electronic databases and the gray literature identified 3613 articles. After exclusions and screening of the full text of 71 articles, 7 remaining eligible articles mapped research activity and identified knowledge gaps in this area. Only 1 study used toileting disability as the primary outcome; it was present in 15% of older adults without dementia living in long term-care facilities (a subgroup that comprised 34% of all residents). The other 6 articles examined factors and treatment of overall activities of daily living (ADL) performance as their primary outcome; in these, toileting disability was added to other difficulties, yielding a summary ADL outcome score. No study reported the incidence, distribution, or factors that affect toileting disability in long-term care; findings of this scoping review suggest a rich research agenda for future investigation. Abstract : Supplemental Digital Content is Available in the Text.The CE test for this article is available online only at the journal website, jwocnonline.com, and the test can be taken online at NursingCenter.com/CE/JWOCN.